A study on visceral fat in relation to anthropometry and lipid profile using dual energy x-ray absorptiometry (DEXA) - Azam, Tengku Balqis Tengku (2018)
Background: Visceral fat plays important role and as an indicator in many health related disease and morbidity. It is defined as body fat that stored within the abdominal cavity around the important internal organs. The fat distribution in the human body is dependent on many factors such as gender, age and ethnicity. The purpose of this study is to determine the correlation between visceral fat and gender, anthropometry; and lipid profile using dual energy x-ray absorptiometry (DEXA). Methodology: Subjects were recruited from Hospital Universiti Sains Malaysia, Kelantan. The inclusion criteria was adult aged 18 to 50 years old. Participants who were pregnant, weighed more than 150kg, had any medical illness requiring anti-lipid medication and had prolonged usage of steroid (more than 2 weeks) were excluded from the study. Anthropometric measurements such as waist circumference, height, weight and BMI were performed. Participants needed to fast for at least for 8 hours for serum lipid profile test. Fasting serum lipid profile result obtained within 3 months before or after DEXA scan was considered valid. DEXA scan was performed to quantify the visceral fat in unit gram (g). Results: Total of 112 participants fulfilled the study criteria. There was significant different of visceral fat between male and female (p=0.024), in which male subjects showed significantly higher VAT than female. It also showed strong correlation between VAT with waist circumference, BMI and weight in both genders. There was significant correlation between VAT with triglycerides (r=0.500, p=0.000), LDL (r=0.222, p=0.019) and HDL (r= -0.440, p=0.000); from which only HDL presented negative correlation with VAT.Conclusion: The findings of the study showed significant different of visceral fat between gender. There is significant correlation between VAT and WC, BMI and serum lipid profile. Thus, WC, BMI and lipid profile can be used as indicator to predict VAT.